Dialogue Between Christian Love and Pancasila Values According to Driyarkara - Bembid, Fransiskus Sailtus (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
This article discusses Christian love and the essence of Pancasila values according to Driyarkara. This secondary research (desk research) uses a qualitative approach with Paul Ricoeur's hermeneutic analysis method. This research critically examines Driyarkara's writings regarding the Pancasila and the Christian Religion. Driyarkara reflected deeply on the essence of the Pancasila as being love for God. Driyarkara's findings regarding love as the essence of the Pancasila will be used as a starting point to explain the relationship between the Pancasila and Christian love. The synthesis of the dialogue between the two becomes the basis for explaining how to become a Pancasila Christian. This article finds several things. First, the point of convergence between Pancasila and Christian love lies in love itself. In the light of the church's faith, Christian love which comes from Christ is the soul, while love as the essence of the Pancasila is its embodiment in the life of the nation and state. Second, the implementation of the Pancasila by Christians is a manifestation of their duty to take part in Christ's mission in the world, namely to proclaim the Kingdom of God which is nothing other than the complete welfare of humans. The research concludes that for a Christian there is no other way to become a Pancasilaist than by truly being a Christian who fundamentally implements Christ's love for others.